Data Analytics and Learning Proceedings of DAL 2018 - Nagabhushan, P.; Guru, D. S.; Shekar, B. H.; Kumar, Y. H. Sharath (Lecture Notes in Networks and Systems,, 2019)
This book presents new theories and working models in the area of data analytics and learning. The papers included in this volume were presented at the first International Conference on Data Analytics and Learning (DAL 2018), which was hosted by the Department of Studies in Computer Science, University of Mysore, India on 30-31 March 2018. The areas covered include pattern recognition, image processing, deep learning, computer vision, data analytics, machine learning, artificial intelligence, and intelligent systems. As such, the book offers a valuable resource for researchers and practitioners alike.